Pengaruh Tingkat Pengetahuan Dan Kepercayaan Mahasiswa Terhadap Penghimpunan Wakaf Uang Di Lembaga Keuangan Syariah Penerima Wakaf Uang (LKS PWU) - Ismamudi; Listian Indriyani Achmad; Sukron Mamun; Aceng Badruzzaman (Jurnal Ekonomi Syariah Pelita Bangsa, 2024)
Cash waqf is done by the waqif in the form of money, securities, checks and others. The hope is that there will be a process of distributing benefits to the community more broadly from private benefits to public benefits. However, the collection is still far from its potential. This study aims to determine the effect of the level of knowledge and trust on the collection of cash waqf at Sharia Financial Institutions Receiving Cash Waqf. Using primary data using a questionnaire. The results of simple linear regression analysis showed the Sig. X1 is 0.000 & 0.05 and the tcount value is 5.211 & ttabel (2.012), X2 has a Sig value. 0.000 and 0.05 and the tcount value is 6.908 and ttabel (2.012). Multiple linear regression analysis obtained Sig value. X1 and X2 simultaneously on Y is 0.000 & lt; 0.05 and the Fcount value is 26.782 > from Ftable (3.20). Indicates that the level of knowledge and trust has a significant impact on the collection of cash waqf. Both partially and simultaneously. It is hoped that there will be further research with different objects and independent variables and more massive socialization of cash waqf literacy so that the collection is significant.